Pregnant woman infected with SARS-COV-2 – diagnosis and treatment - Borowik, Joanna; Kaziród, Karolina; Miturski, Andrzej; Semczuk-Sikora, Anna (Journal of Education, Health and Sport, 2022)
Introduction: COVID-19 is an infection caused by the new SARS-CoV-2 virus. In pregnant women with COVID-19, compared to non-pregnant women, there is an increased risk of a severe course of the infection. Pregnant women are more often hospitalized in the Intensive Care Unit and require mechanical ventilation. In the course of COVID-19 infection, pregnant women have a greater risk of miscarriage, premature birth or having a baby with low birth weight, compared to their healthy pregnancy peers. The aim of the study: To present, based on the available literature, the principles of management of a pregnant woman infected with SARS-CoV-2 virus. State of knowledge: The evidence of infection is the detection of the virus in the clinical specimen confirmed by PCR. Chest computer tomography can be useful in diagnosis, especially when the PCR test result is negative. Particular attention should be paid to pharmacological treatment, which should be both effective and safe for the fetus. Certain antiviral and anti-inflammatory drugs as well as anticoagulants drugs are used in COVID-19 therapy. Oxygen and fluid therapy is also important. The condition of the fetus should be monitored regularly. It is recommended to measure the fetal heart rate, perform cardiotocography, pregnancy ultrasound and assess the volume of amniotic fluid. The decision about the time and method of delivery should be made individually on the basis of obstetric indications and the maternal-fetal condition. Summary: The therapy of a pregnant patient infected with SARS-CoV-2 should be adjusted individually depending on the woman's health condition. In therapeutic interventions, the welfare of both the mother and the fetus should be taken into account.